Effect of retrogression and re-ageing treatment on stressed component of wrought 6061 aluminium alloy / Rasdi Deraman and Sunara Purwadaria - Deraman, Rasdi; Purwadaria, Sunara (2008)
This paper presents the effect of different heat treated to mechanical properties and microstructure of stressed component of wrought 6061 aluminium alloy. This alloy is known for their medium strength and high durability. These properties have made them useful in the aerospace, automobile industries and suitable for extrusion components, Precipitation hardening is a process to increase the strength and hardness by which aluminium alloys are heat and solution treated followed by artificial ageing (T6 temper), The strength of this alloy in T6 temper condition is increased but susceptible to fracture because of the applied stress. Over-ageing tempers was developed to improve stress resistance of wrought aluminium alloys by modifying the microstructure but significantly will reduce the mechanical strength. Retrogression and re-ageing (RRA) treatment was applied in order to minimise the wrought 6061 aluminium alloy prone to stress effect, while maintaining a higher mechanical properties, In this study the dumb-bell specimen of wrought 6061 aluminium alloy was retrogressed in stirred of engine oil followed by immediate quenched in plain water at room temperature and then re-ageing in an oven. The fractured surface of the specimens were analysed using Scanning Electron Microscopy (SEM) to investigate the microstructures changed. The tensile and indentation test results for T6 temper followed by RRA treatment revealed that the strength and hardness of wrought 6061 aluminium alloy are much better compare to over-ageing results.